AKTIVITAS ANTIKANKER GENISTEIN SEBAGAI PERUSAK G2 ARREST YANG DIINDUKSI KURKUMIN PADA SEL KANKER PAYUDARA T47D - , ESTI DYAH UTAMI; , Prof. Dra. Sismindari, SU., Ph.D., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Cancer is the leading cause of death in the worldwide. More than 50% of cancer cells have defects in the p53 gene. Cancer cells with p53 mutations may be resistant to antineoplastic drugs that produce DNA damage, urge the finding of new drugs having better mechanisms. Conventional chemotherapeutic agents have not provided satisfactory results and may cause side effects, this encourages the use of natural ingredients as an alternative of cancer therapy. Curcumin (diferuloylmethane) is reported to induce G2 phase cell cycle arrest in some cancer cell lines. Other study reported that Genistein inhibited phosphorylation of CDK1, gene involved during G2/M transition and thus could function as G2 checkpoint abrogator. Abrogation of G2 arrest is one of alternative strategy which could selectively kill cancer cells with mutated p53, and potentially be combined with DNA damaging agent such as curcumin. Anticancer activity of curcumin can be improved by the addition of piperine. The aims of this research is to evaluate the ability of curcumin to induce G2 arrest in human breast cancer T47D cells which is mutant for p53 function, to study the ability of Genistein to abrogate the cell cycle arrest induced by curcumin in T47D, to evaluate the effect of genistein to enhance the T47D cell death following curcumin treatment, and to determine the effect of piperine on T47D cell cycle profile. The effect of curcumin to induce G2 arrest, the effect of genistein to abrogate the G2 arrest induced by curcumin, and effect of piperine on cell cycle profile was studied in T47D cells by flowcytometry assay. The effect of genistein to enhance the T47D cell death following curcumin treatment were determined by MTT assay. In this research, curcumin induced G2 arrest at the optimum concentration of 10 Î¼M when it was administered on T47D cell having p53 mutation. Increasing concentration up to 30 Î¼M did not further increase the G2 phase cell population. Genistein abrogated G2 arrest induced by curcumin in T47D cells, with the optimum concentration of 20 Î¼M. Genistein also increased T47D cell death with a significant difference (sig = 0.000) compared to single curcumin treatment. Piperine up to levels 50 Î¼M did not affect T47D cell cycle profile.